The consequences of air flow on the distribution of aqueous species during dielectric barrier discharge treatment of thin water layers. (9th September 2016) - Tian, Wei; Lietz, Amanda M; Kushner, Mark J
Abstract: The desired outcomes of wet tissue treatment by dielectric barrier discharges (DBDs) strongly depend on the integrated fluences of reactive species incident onto the tissue, which are determined by power, frequency and treatment time. The reactivity produced by such plasmas is often expected to be proportional to treatment time due to the accumulation of radicals in the liquid over the tissue. However, one of the typically uncontrolled parameters in DBD treatment of liquids and tissue is gas flow, which could affect the delivery of plasma produced radicals to the tissue. Gas flow can redistribute long-lived, plasma produced gas phase species prior to solvating in the liquid, while not greatly affecting the solvation of short-lived species. Gas flow can therefore potentially be a control mechanism for tailoring the fluences of reactive species to the tissue. In this paper, we report on a computational investigation of the consequences of gas flow on treatment of liquid layers covering tissue by atmospheric DBDs by up to 100 pulses. We found that gas flow (through residence time of the gas) can control the production of gas phase species requiring many collisions to form, such as reactive nitrogen species (RNS). The resulting solvation of the RNS in turn controls the production of aqueous species such as NO 3aq − and ONOO aq − (aq denotes an aqueous species). With the exception of O3 and O3aq, reactive oxygen species (ROS) are less sensitive to gas flow, and so OHaq and H2 O2aq, are determined primarily by discharge properties.